Knowledge Transfer as a Mechanism of Organizational Transition - Berthon, Boris (International Transitions, 2025)
In a rapidly evolving world marked by technological acceleration and global challenges such as climate change and resource depletion, organizations face increasing pressure to adapt. This article explores the role of knowledge transfer as a strategic mechanism enabling deep organizational transitions. Drawing on evolutionary theories of adaptation and contemporary research in strategic management and transition studies, the article argues that beyond adapting products or services, organizations must undertake systemic transformations often involving a reconfiguration of their business models. Knowledge transfer thus emerges as an essential lever, enabling the dissemination, appropriation, and renewal of organizational capabilities. By situating this dynamic within the interdisciplinary field of sustainability transitions, the article highlights the potential of knowledge transfer to strengthen the resilience and long-term viability of organizations operating in complex and uncertain environments.